Memoirs of Lady Hyegyong : the Autobiographical Writings of a Crown Princess of Eighteenth-Century Korea. - Haboush, JaHyun Kim (University of California Press, 2013)
Lady Hyegyong's memoirs, which recount the chilling murder of her husband by his father, form one of the best known and most popular classics of Korean literature. From 1795 until 1805 Lady Hyegyong composed this masterpiece, depicting a court life Shakespearean in its pathos, drama, and grandeur. Presented in its social, cultural, and historical contexts, this first complete English translation opens a door into a world teeming with conflicting passions, political intrigue, and the daily preoccupations of a deeply intelligent and articulate woman. JaHyun Kim Haboush's accurate, fluid t.